What mediates the effects of market orientation on performance?: the case of high technology companies in South Africa - Heyns-Nell, Charléne (Graduate School of Business (GSB), 2024)
Conventional market orientation philosophy holds that behavioural and philosophical cultural aspects of marketing are fundamental to an organisation. Prior research on strategic orientation in marketing research has focused on the construct of market orientation, which has been shown to have strong positive relations on business performance. In the present research, the effects of market orientation on performance are assessed concurrently with two other types of strategic orientation: technology orientation and learning orientation. In addition, we assess the mediating properties of entrepreneurship and innovativeness on the relationship of these three types of strategic orientation on business performance. Two hundred South African high technology firms participated in the present research. Contrary to portrayals of high technology firms as start-ups run by entrepreneurs, many high technology companies in South Africa are firmly established institutions that practise market orientation and strategic planning, for that matter. Because the institutional context of emerging markets differs considerably from that of the high-income countries in which market orientation theory has been proposed and primarily tested, a meta-analysis of prior market orientation studies conducted in 24 emerging markets was conducted, using meta-analysis techniques recommended by Lipsey and Wilson (2001). The results of the meta-analysis results provide insights into market orientation in the emerging market context. Drawing on extant theory and the meta-analysis results, the theorized relations are tested systematically in a structural equation model. The findings of this study suggest that top management emphasis of market-orientation creates an environment in which technology orientation and learning orientation also thrive. This improves business performance directly and through improved innovation and entrepreneurship.